التسوية الإدارية لإشكالات المسح العقاري في التشريع الجزائري - محمد، بوزيد (جامعة الوادي University of El Oued, 2025)
قضايا المسح العقاري العام في الجزائر، حيث تأثرت العملية باتساع مساحة البلاد، والصعوبات المالية والفنية، وضعف كفاءة الموظفين. إضافةً إلى ذلك، تواجه العملية عقبات قانونية وإدارية تعيق تقدمها وتبطئ إنجازها. واقترحت الدراسة تعزيز رقمنة القطاع العقاري وتحديث الإطار القانوني، بالإضافة إلى تحسين آليات التسوية الإدارية التي أقرها المشرع. وتهدف هذه الخطوة إلى تخفيف الضغط على القضاء من خلال اللجوء إلى التسوية القضائية لحل النزاعات العالقة. وتؤكد الدراسة على أهمية تعزيز التسوية الإدارية لضمان فعاليتها وسلامة الإجراءات مع حماية حقوق الأفراد. he issues of the generalland survey in Algeria, where the process has been affected bythe country's large area, financial and technical difficulties, and alack ofefficiency among personnel. Additionally, the processfaces legal and administrative obstacles that hinder progress andslow down completion. The study suggested enhancing thedigitization of the real estate sector and updating the legalframework, as well as improving the administrative settlement mechanisms introduced by the legislator. This step aims toalleviate pressure on the judiciary by involving judicial settlementto resolve unresolved disputes. The study emphasizes theimportance of strengthening administrative settlement to ensure its effectiveness and the integrity of procedures whilesafeguarding individual rights.
قانون عقاري
Keywords: مسح الأراضي العام، مشاكل المسح، رقمنة قطاع العقارات، التسوية الإدارية.; General Land Survey; Survey Problems; Digitalization of Real Estate Sector; Administrative Settlement.